(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
This paper comments some aspects of the Hispanic collection of proverbs which appeared when the author worked on his Diccionario de paremias cervantinas (Alcalá de Henares, 2015). It points out the importance of putting in his frame the apogee of the collections of proverbs in the XVI and XVII centuries in the movement of dignifying the vulgar languages which took place in this time. From here we comment two outstanding aspects of the Diccionario : the study of the proverbs in their diachrony and their consideration as a cultural phenomenon of the language. In this way, some characteristics of the Hispanic collection of proverbs are revealed: the cultural interference, the difficulty of defining what a version is, the distinction between varying and innovation, the dating of the proverbs and the contaminations of different lexical forms.